2010
DOI: 10.1002/glia.21009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of axon degeneration on oligodendrocyte lineage cells: Dorsal rhizotomy evokes a repair response while axon degeneration rostral to spinal contusion induces both repair and apoptosis

Abstract: Wallerian degeneration in the dorsal columns (DC) after spinal cord injury (SCI) is associated with microglial activation and prolonged oligodendrocyte (OL) apoptosis that may contribute to demyelination and dysfunction after SCI. But, there is an increase in OL lineage cells after SCI that may represent a reparative response, and there is evidence for remyelination after SCI. To assess the role of axonal degeneration per se in OL apoptosis and proliferation, we cut the L2-S2 dorsal roots producing massive axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 92 publications
1
37
0
Order By: Relevance
“…One explanation for this difference is the unique oxidative microenvironment created by spinal contusion may prevent maximal proliferation. For example,Sun et al (2010) showed that RNA oxidation is significantly increased in oligodendrocytes near contusion injuries within 1h but oxidation was not present around pure axon degeneration injuries. In our study, contusion tissue supported later OPC division since NG2/BrdU cells increased 9-fold between 1 – 7dpi.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this difference is the unique oxidative microenvironment created by spinal contusion may prevent maximal proliferation. For example,Sun et al (2010) showed that RNA oxidation is significantly increased in oligodendrocytes near contusion injuries within 1h but oxidation was not present around pure axon degeneration injuries. In our study, contusion tissue supported later OPC division since NG2/BrdU cells increased 9-fold between 1 – 7dpi.…”
Section: Discussionmentioning
confidence: 99%
“…To observe the dynamic changes occurring in mature oligodendrocytes during epileptogenesis, immunohistochemistry was used to study the expression of CC1, a marker of mature oligodendrocytes (Flygt et al, 2013;Sun et al, 2010). Fig.…”
Section: Oligodendrocytes In Rats Subjected To Lithiumpilocarpine-indmentioning
confidence: 99%
“…In rodents, this diminution of OLs occurs several segments away from the epicenter, extending rostro-caudally along the degenerating axon tracts [6,8]. However, a recent study determined that axon degeneration alone (in the absence of trauma) was not sufficient to kill OLs and in fact evoked OPC proliferation and new OL formation [30]. The authors contrasted this response to OL apoptosis rostral to spinal contusion in which they noted that markers of oxidative stress were present in OLs following contusion injury but not dorsal rhizotomy.…”
Section: Early Mechanisms Of Ol Lossmentioning
confidence: 99%